PENERAPAN ORGANISASI PEMBELAJAR DI RUMAH SAKIT PANTI RAHAYU, PURWODADI, JAWA TENGAH - , IKA WAHYU PRATIWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Panti Rahayu hospital was the first hospital in the city of Purwodadi which was established in 1976 and had become the only hospital that was existing in that time. Moreover, the city are growing up and the public facilities and infrastructures are enhanced to develop the city, one of them is in the health service. Many of new hospitals and private physician practices are built in there. On the other side, the environment changing is also occurred by the need of the service health for the people in Purwodadi which is more diverse from to time to time and the government policy for health service often changes in the certain period of time. Furthermore, the environment changing makes Panti Rahayu hospital to be aware to fulfill the demands of the environment in order to maintain the existence of the organization. The first action that is performed by Panti Rahayu hospital is changing the organization's vision, but It is difficult to achieve because a lot of obstacles that must be faced by the organization. Therefore, in order to overcome the problems, Panti Rahayu hospital pushed their selves to be an organizational learning. The aim of the study is to explore how the implementation organizational learning of the Panti Rahayu hospital, Purwodadi, Jawa Tengah in order to face the environment changing in Purwodadi. This study used qualitative research design by the case study method which was focused on the question of âhowâ or âwhyâ of an event or the case could be occurred. The data collection technique of case study used many information resources such as observation, interview, audio visual materials, documents, and reports. Based on the result of the study, the implementation of organizational learning in Panti Rahayu hospital is in the form of the fifth behaviors, namely transfer knowledge, value empowerment, making conducive environment, corrective action, and internal process empowerment. Moreover, the successful of the implementation of those behaviors cannot be separated by the leaders in Panti Rahayu who act as role models to their employees, especially in giving examples how those behaviors are implemented in daily life of the organization. Finally, the implementation of those behaviors are not only as a tools to maintain the existence of organization in the midst of environmental change, but also strengthening the concept of âGajah Menariâ which is held by Panti Rahayu Hospital. Key Words: Organizational Learning, learning process, hospital